The current state of the medical and physical education service in Ryazan region: The main trends and ways of development - I. I. Manakin; E. S. Manakina (National Electronic Information Consortium (NEICON), 2020)
Study objective: to analyze the activities of the regional Ryazan medical and physical dispensary in health maintaining and promoting in various medical and social groups and identify ways to improve the dispensary medical services quality. Materials and methods: a timing study of specialists, registry and laboratory workers involved in an in-depth examination at the medical exercises dispensary in Ryazan region. The 14-day study involved 20 specialists and 50 patients who underwent an in-depth medical examination. Results:We identifies the specialists working time consumption to develop and implement an action plan to reduce medical visit duration, the time spent by athletes at the examination stage and, accordingly, to increase the institution capacity. Conclusions: there is an obvious need to modernize medical support for people involved in physical culture and sports in the Ryazan region due to a significant lag in the growth rates of physiotherapy and sports medicine services from the rate of new sports facilities are commissioned and a significant increase in the number of athletes involved in physical culture and sports.